Optimised Stable Lighting Strengthens Circadian Clock Gene Rhythmicity in Equine Hair Follicles - Aileen Collery; John A. Browne; Christiane O’Brien; John T. Sheridan; Barbara A. Murphy (Animals, 2023)
Hair follicles (HF) represent a useful tissue for monitoring the circadian clock in mammals. Irregular light exposure causes circadian disruption and represents a welfare concern for stabled horses. We aimed to evaluate the impact of two stable lighting regimes on circadian clock gene rhythmicity in HF from racehorses. Two groups of five Thoroughbred racehorses in training at a commercial racehorse yard were exposed to standard incandescent light or a customized LED lighting system. The control group received light from incandescent bulbs used according to standard yard practice. The treatment group received timed, blue-enriched white LED light by day and dim red LED light at night. On weeks 0 and 20, mane hairs were collected at 4 h intervals for 24 h. Samples were stored in RNAlater at −20 °C. RNA was isolated and samples interrogated by quantitative PCR for the core clock genes: ARNTL, CRY1, PER1, PER2, NR1D2, and the clock-controlled gene DBP. Cosinor analyses revealed 24 h rhythmicity for NR1D2 and PER2 and approached significance for CRY1 (p = 0.013, p = 0.013, and p = 0.051, respectively) in week 20 in the treatment group only. No rhythmicity was detected in week 0 or in week 20 in the HF of control horses. Results suggest that lighting practices in racehorse stables may be improved to better stimulate optimum functioning of the circadian system.